PERFORMANCE MEASUREMENT AND BUSINESS STRATEGY THROUGH BALANCE SCORECARD APPROACH AND SWOT ANALYSIS (STUDY AT PT. INTI NUSA PERMATA) - Tirtayasa, Yohan; Shilul Imaroh, Tukhas (Dinasti International Journal of Management Science, 2021)
The purposes of this research were to determine the company's performance as measured by the Balanced Scorecard approach, as well as to make recommendations for strategy to enhance the company's performance in developing PT. Inti Nusa Permata based on SWOT analysis. The data analysis technique was carried out by SWOT analysis and the preparation of a balanced scorecard matrix which is measured into 4 perspectives, namely financial perspective, customer perspective, internal business process perspective, and growth and learning perspective. The study's findings suggest that the company is performing well in terms of customer satisfaction, internal business processes, and growth and learning. However, PT. Inti Nusa Permata's financial performance is poor, particularly in terms of short-term financial capacity. The results of the balanced scorecard approach used to assess the company's performance reveal that PT. Inti Nusa Permata has a very good performance. The company's strategy mapping demonstrates that PT. Inti Nusa Permata is in quadrant I, adopting the S-O (Strength-Opportunity) method, which aims to leverage on existing opportunities by utilizing the company's strengths.